Economic implications of further harmonisation of electronic communications regulation in the EU - J. Scott Marcus; Tseveen Gantumur (International Telecommunications Society (ITS), 2015)
A European debate over measures ostensibly to fully achieve a single market for electronic communications across the EU was brought to a head by the European Commission's 2013 proposed Telecoms Single Market (TSM) legislative package. The Commission apparently hoped to achieve a Single European Market for electronic communications solely by means of regulatory harmonisation. The Commission's proposal can serve as the basis for important reflections on harmonisation at European level. Why do we seek regulatory harmonisation? How does harmonisation differ from uniformity? What benefits flow from centralisation, and what benefits from decentralisation? Is the European Union in fact a Union? To what extent do the Member States differ from one another in ways that are not readily altered in the near term? What economic consequences (beyond those already achieved by the current regulatory framework) might be expected from more extensive harmonisation of European electronic communication? What do these considerations tell us about the degree of harmonisation that is desirable, and the degree that is realistically achievable? The approach taken in this paper can help to clarify thinking as to costs and benefits of stronger harmonisation or centralisation of electronic communications regulation, but we do not claim that we have evaluated every regulatory possibility, nor that our assessment is definitive. It is a thought exercise that is meant to help clarify the bounds to what can be achieved solely by means of regulatory harmonisation.
Keywords: 330